2017
DOI: 10.1002/cpmc.26
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii: Laboratory Maintenance and Growth

Abstract: Toxoplasma gondii is a highly successful Apicomplexan protozoan capable of infecting any warm-blooded animal worldwide. In humans, Toxoplasma infections are life-long with approximately one-third of the world’s population chronically infected. Although normally controlled by the host immune system, T. gondii infection can lead to a variety of clinical outcomes in individuals with immature or suppressed immune systems. After penetrating the intestine, parasites rapidly disseminate throughout the body and stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 60 publications
0
27
0
Order By: Relevance
“…All procedures were performed in accordance with the laws and conditions of the Guide for the Care and Use of Laboratory Animals and Institutional Animal Ethics Committee guidelines of Shanxi Medical University. T. gondii tachyzoites (RH strain) were kindly provided by the Peking University Health Science Center and were maintained via serial intraperitoneal passage in BALB/c mice [11].…”
Section: Methodsmentioning
confidence: 99%
“…All procedures were performed in accordance with the laws and conditions of the Guide for the Care and Use of Laboratory Animals and Institutional Animal Ethics Committee guidelines of Shanxi Medical University. T. gondii tachyzoites (RH strain) were kindly provided by the Peking University Health Science Center and were maintained via serial intraperitoneal passage in BALB/c mice [11].…”
Section: Methodsmentioning
confidence: 99%
“…Before being employed in the current study, the tachyzoites were peritoneally injected (5 × 10 4 parasites per mouse) into naive mice. The second generation of tachyzoites were then recovered from the mice (ensure they are unlysed), washed and resuspended to 5 × 10 6 parasites/ml in an invasion Endo buffer (100 ml physiological saline (NaCl) and 100 µL heparin (48,49). Transgenic parasites used were GFP-labeled and were therefore viewed under fluorescent microscope.…”
Section: Parasite Strainmentioning
confidence: 99%
“…We implement our network on TensorFlow framework [Keeton and Roscoe, 2016] with Tesla K40C and 128G memory in Ubuntu 16.04 system, and use the Adam solver [Kingma and Ba, 2014] for FCGAN network with a learning rate of 2e-4 and closely follow the settings of Cycle GAN and Vgg Network to train generators, discriminators and feature extractors. After jointly training for 4000 epoches, we apply early stop when the fuzzy loss no longer decreases for about 5 epochs (usually takes 4000 jointly training epochs to reach a desired point).…”
Section: Training Detailsmentioning
confidence: 99%
“…T oxoplasma gondii (T.gondii) is an ubiquitous, single cell protozoan parasite that can infect all warm-blooded animals as well as one-third of human population worldwide [Khan and Grigg, 2017]. Most infections in humans are life-long and several studies have suggested that such infections may contribute to severe neurological and psychiatric symptoms.…”
Section: Introductionmentioning
confidence: 99%